Anxiety in Primary Health Care professionals during the COVID-19 pandemic - Saliba, Tânia Adas [UNESP]; Nascimento, Carolina Carvalho Menez Pinto [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
Fundaments: The imbalance between professional duty and fear during the in COVID-19 pandemic caused emotional instability in health workers. Objectives: To assess anxiety in Primary Health Care (PHC) professionals and associated factors and analyze the positive and negative perceptions of the pandemic. Methodology: This is a descriptive-exploratory, quantitative and qualitative cross-sectional study, with PHC professionals, in a municipality in the state of São Paulo, Brazil, from December 2020 to March 2021. Descriptive statistics were carried out, and the chi-square test was applied at the 5% level. For textual content, lexical analysis was carried out by Descending Hierarchical Classification. Main results: It was identified that more than 50% of participants had anxiety, and it was associated with having contracted COVID-19 (p-value = 0.0327), interference with daily activities (p-value < 0.0001) and occupation (p-value < 0.0001) -value = 0.0483). Negative points were mental health, working conditions, service and behavior. Positive points were biosafety, self-care and personal protective equipment use. Conclusions: Most PHC professionals presented anxiety, and it was associated with sociodemographic factors. The pandemic brought positive and negative points from PHC professionals’ perspective.
Keywords: Anxiety; Mental health; Occupational health; Pandemics; Primary health care